2019
DOI: 10.5194/acp-19-5791-2019
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional contributions to fine particulate matter in the 18 cities of Sichuan Basin, southwestern China

Abstract: Abstract. The Sichuan Basin (SCB) is one of the regions suffering from severe air pollution in China, but fewer studies have been conducted for this region than for the more developed regions in eastern and northern China. In this study, a source-oriented version of the Community Multiscale Air Quality (CMAQ) model was used to quantify contributions from nine regions to PM2.5 (i.e., particulate matter, PM, with an aerodynamic diameter less than 2.5 µm) and its components in the 18 cities within the SCB in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 63 publications
3
31
0
1
Order By: Relevance
“…This finding also indicates that the instability of local pollutant emissions and regional transport during cold months was affected by meteorological conditions (Li et al, 2017;Ji et al, 2018). The large variation amplitude of pollutants in different months, similar to the changes in the Beijing-Tianjin-Hebei region of northern China and Chengdu, is due to the accumulation and removal of pollution by meteorological conditions and pollutant emissions (Ji et al, 2019;Qin et al, 2019;.…”
Section: Monthly and Seasonal Variationsmentioning
confidence: 64%
“…This finding also indicates that the instability of local pollutant emissions and regional transport during cold months was affected by meteorological conditions (Li et al, 2017;Ji et al, 2018). The large variation amplitude of pollutants in different months, similar to the changes in the Beijing-Tianjin-Hebei region of northern China and Chengdu, is due to the accumulation and removal of pollution by meteorological conditions and pollutant emissions (Ji et al, 2019;Qin et al, 2019;.…”
Section: Monthly and Seasonal Variationsmentioning
confidence: 64%
“…It should be declared that out of the benchmark does not mean failure of the prediction as the benchmark value is constructed on the MM5 simulations for the eastern United States with finer grid resolutions (12 km and 4 km). The WRF model predictions are normally reliable since the model performance statistics are like other WRF studies applied over China (Zhang et al, 2012a;Qiao et al, 2019;Hu et al, 2016). Tables S2 and S3 show the model performance statistics of PM 2.5 from the two emission reduction cases.…”
Section: Model Validationmentioning
confidence: 90%
“…However, the NMBs were within a reasonable range (> −25 %) during EP1 but presented much lower values (> 40 %) during the other periods. Thus, this demonstrates that original OBB emissions as well as other sources can allow the model to capture spatiotemporal variations in PM 2.5 concentrations for normal situations without significant impacts by OBB in most of the provinces, as recorded by previous studies (Hu et al, 2015;Liu et al, 2016;Qiao et al, 2019), whereas the model failed to reproduce the rapid outbreak of PM 2.5 concentrations for this OBB event, especially during EP2 in Henan and Anhui. This result shows the need to derive optimal OBB emissions using this constraining method.…”
Section: Constrained Optimal Obb Emissionsmentioning
confidence: 53%
“…Open crop straw burning (OCSB), as a crucial part of OBB, generally occurs on a large spatial scale during the harvest seasons in regions with intensive agricultural activities, because it is still the most effective, efficient, and economical measure to dispose of open crop straw (Li et al, 2007;Qin and Xie, 2011;Zhang et al, 2017Zhang et al, , 2018Zhang et al, , 2019Xu et al, 2019). Previous studies showed that emissions from OCSB accounted for more than 80 % of those from OBB over China during the past decade.…”
Section: Introductionmentioning
confidence: 99%